Business School Research: Excellence, Academic Quality and Positive Impact - Eric Cornuel; Howard Thomas; Matthew Wood (Routledge, 2024)
This second book in the EFMD Management Education series explores business schools' increasing focus on, and search for, meaningful societal and economic research impact. This involves, in particular, co-operation and collaboration in both knowledge creation and implementation of the findings of academic research in practice. Business schools have a critical role to play in `rewiring' our missions for research relevance, impact and reach, and in recognising needs and addressing real issues of society and economy. With cases from a range of international business schools, the book doesn't simply highlight the need for the dominant research model in business schools to evolve, but illustrates how this can happen in practice. In so doing, it opens the discussion on how the business school can contribute in very real ways to solving global and complex challenges such as climate change, rising inequalities, international isolationism, eroding democratic systems, and the spread of fake news. These are goals that the EFMD has championed since its inception, and this book will be of value and interest to policy makers and business leaders seeking insight into how management education will be shaped to support business and wider society, as well as those working in business schools and higher education leaders. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.
Keywords: 650; Management education; Business schools; Business research impact; Business school leadership; Social impact; Higher education; Deans